Rancang Bangun Aplikasi Sastra Lisan (Lawas) Khas Sumbawa Berbasis Android - Haryati Haryati; Shinta Esabella (Universitas Bumigora, 2019)
This study aims to convert data from Sumbawa Lawas (Oral Poetry) which are currently preserved in the form of books for changes to digital forms. This study uses spiral software development methods and programming languages using Android Studion 2.3.3 as well as SQLite databases targeting Android users version 5.0 (Lollipop). The method of data collection uses a literature study technique with data sources from Boan Lawas book by publisher Usman Amin Trussmedia with ISBN 978-602-0992-88-4 and uses black box testing methods whose testing is done by testing software in terms of functionality. The results of this study are the Android-based for Sumbawa Lawas Application that can be accessed through the Play Store which is equipped with history, type, poetry and meaning and about the application so that it can provide information for Sumbawa indigenous people and people outside Sumbawa.